010 Satisfaction Rates of Inflatable Penile Prosthesis in Men Who Have Sex With Men. (1st May 2022) - La, J.; Loeb, C.; Chung, E.; Gross, M.; Hatzichristodoulou, G.; Park, S.H.; Perito, P.; Sarmiento, A.S.; van Renterghem, K.; Yafi, F.
ABSTRACT: Introduction: Men with erectile dysfunction have high patient satisfaction after placement of inflatable penile prostheses (IPP), but the impact on satisfaction and quality of life has never been studied in men who have sex with men (MSM) with erectile dysfunction. Objective: To assess the satisfaction rates and quality of life of MSM after placement of IPP for erectile dysfunction. Methods: A multi-institutional, retrospective study enrolled adult men who self-identified as MSM and underwent inflatable penile prosthesis placement with either AMS 700 TM LGX, AMS 700 TM CX or Coloplast Titan TM models. Two questionnaires were administered at one timepoint post-operatively. The Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) is a 11-item validated questionnaire measured on a 0-100 scale. The Quality of Life and Sexuality with Penile Prosthesis (QoLSPP) is a 16-item questionnaire subcategorized into 4 domains: functional, relational, social, and personal. Fisher's exact test and paired t-test were used to calculate significance with p-values <0.05 considered significant. Results: Forty-nine MSM were assessed with a median age of 62 years (interquartile range [IQR], 53-69) with median follow-up of 14.2 months (IQR, 8.1-21.9). AMS 700 TM LGX, AMS 700 TM CX or Coloplast Titan TM IPPs were placed 2, 2 and 45 men, respectively. For the entire cohort, the median EDITS score was 93 (IQR, 91-95) and the median QoLSPP scores each domain were functional 23/25 (IQR, 22-24), relational 17/20 (IQR, 15-18), social 15/15 (12-15), personal 18/20 (IQR, 17-19) with a total of 72/80 (IQR, 68-76). Conclusions: MSM report high satisfaction rates and quality of life after IPP placement for ED. Disclosure: Work supported by industry: no. A consultant, employee (part time or full time) or shareholder is among the authors (Coloplast, Boston Scientific/AMS, Urofill, ).